Islamic Marketing In The Context Of Buying And Selling - syakir, khalifa; Rahadian; Leonita Siwiyanti, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Marketing in the context of Islam that is appropriate is marketing that follows the teachings and sunnah of the Prophet SAW. In the work environment, the attitude of maintaining honesty must be instilled so that consumers obtain various information about the products and services sold. The Prophet (peace be upon him) always guaranteed himself what he sold to his customers. The type of research used in this writing is literature research and the author collects information including books, scientific articles, research-related sources, and sources collected. Marketing is a science that is developing very quickly. So is the marketing department of a company with a very strategic position. This can be understood because marketing is a benchmark for a company's success. When a company/industry produces a product or service but cannot market it, the company it manages faces problems. Therefore, profits are the spearhead of the survival of a company. Marketing is a social process allowing individuals and groups to offer, produce, and exchange products and services freely. The results of this study can be seen that in the integration of Islamic marketing in the context of buying and selling, consumers, individuals, and groups will get their needs and desires by creating offers and exchanging products or value with other parties.